Method for preparing gradient MWCNTs-Ti (C, N)-based metal ceramic through spark plasma sintering

By using discharge plasma sintering technology in Ti(C,N)-based metal cermets, the content of multi-wall carbon nanotubes is increased layer by layer to form a gradient structure, which solves the problem of large differences in microstructure unevenness and fracture toughness of ceramics, which is significantly Improves its performance.

CN119457069APending Publication Date: 2025-02-18HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411591397.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The microstructure of Ti(C,N)-based cermets is uneven, resulting in large differences in fracture toughness at different locations, limiting their widespread application.

Method used

Discharge plasma sintering technology is used to increase the content of multi-wall carbon nanotubes layer by layer according to the gradient path, optimize the alloy microstructure to form gradient MWCNTs-Ti(C,N)-based cermet.

Benefits of technology

The microstructure uniformity of metal cermets is improved, the fracture toughness and hardness at different locations are relatively close, the alloy has superior performance, and further improves the fracture toughness and hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457069A_ABST
    Figure CN119457069A_ABST
Patent Text Reader

Abstract

A method for preparing gradient MWCNTs-Ti (C, N)-based metal ceramic through spark plasma sintering relates to the field of powder metallurgy and comprises the following steps that S1, N kinds of mixed powder composed of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are prepared, N is larger than or equal to 3, and the mass percent of the multi-walled carbon nanotubes in the N kinds of mixed powder is changed in a gradient mode; s2, the mixed powder is laid layer by layer according to the change gradient of the multi-wall carbon nanotubes, and the obtained N layers of mixed powder are pre-pressed and formed to obtain a metal ceramic blank; and S3, current is applied to the side, with the lowest multi-walled carbon nanotube content, of the metal ceramic green body, spark plasma sintering is conducted on the metal ceramic green body, and the gradient MWCNTs-Ti (C, N)-based metal ceramic is obtained. The method is used for solving the technical problems that a metal ceramic microstructure is not uniform, and the fracture toughness difference of different positions is large.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder metallurgy, in particular to a method for preparing gradient MWCNTs-Ti (C, N) based cermets by spark plasma sintering. Background Art

[0002] Tungsten carbide cemented carbide has excellent mechanical properties, such as high hardness and high strength, so it is widely used in cutting tools, oil mining and other fields. However, the performance of tungsten carbide shows obvious degradation at high temperatures, which limits its application in high temperature processing. At the same time, tungsten is also regarded as a strategic resource, and the reserves of titanium are dozens of times that of tungsten. Therefore, Ti (C, N) based cermets are regarded as an ideal substitute for WC cemented carbide. However, compared with tungsten carbide, the fracture toughness of Ti (C, N) based cermets is low, only 6-9MPa·m 1 / 2 , while the fracture toughness of tungsten carbide-based cemented carbide is 9-16MPa·m 1 / 2 , which greatly limits the application of Ti(C,N)-based cermets.

[0003] The main reason for the poor toughness of Ti(C,N)-based cermets is that the wettability of the hard phase and the metal bonding phase in Ti(C,N)-based cermets is poor, resulting in its strength and toughness being inferior to those of WC cemented carbide. In order to improve the above-mentioned wettability and enhance the fracture toughness of Ti(C,N)-based cermets, carbides such as WC and Mo2C are often used as additives in the prior art. The addition of these carbides improves the wettability between the metal phase and the Ti(C,N) grains to a certain extent, hinders the growth of grains, and improves the density and mechanical properties of Ti(C,N)-based cermets; in addition to these carbides, nanomaterials are also often used as reinforcing and toughening materials, such as multi-walled carbon nanotubes and graphene.

[0004] After adding reinforcing and toughening materials, although the overall hardness and fracture toughness of the prepared metal ceramics have been improved to a certain extent, the microstructure of the metal ceramics is uneven and the fracture toughness at different positions varies greatly, which still limits the widespread application of Ti(C,N)-based metal ceramics. Summary of the invention

[0005] The invention provides a method for preparing gradient MWCNTs-Ti (C, N) based cermet by spark plasma sintering, so as to solve the technical problems that the cermet microstructure is uneven and the fracture toughness at different positions is greatly different.

[0006] In order to achieve the above object, the specific scheme adopted by the present invention is: a method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering, comprising the following steps:

[0007] S1: preparing N kinds of mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes, N≧3, and the mass percentage of the multi-walled carbon nanotubes in the N kinds of mixed powders changes in a gradient;

[0008] S2: laying the mixed powder layer by layer according to the change gradient of the multi-walled carbon nanotubes, and pre-pressing the obtained N layers of mixed powder to obtain a metal ceramic body;

[0009] S3: applying current from the side of the metal ceramic body with the lowest multi-walled carbon nanotube content to perform spark plasma sintering on the metal ceramic body to obtain the gradient MWCNTs-Ti(C,N) based metal ceramic.

[0010] As a further optimization of the above technical solution: according to mass percentage, the mixed powder consists of 64.2-65% titanium carbonitride, 22.4-23.2% tungsten carbide, 8% cobalt, 3.6-4.4% molybdenum carbide and 0.2-0.6% multi-walled carbon nanotubes.

[0011] As a further optimization of the above technical solution: the change gradient of the multi-walled carbon nanotubes is 0.1% or 0.2%.

[0012] As a further optimization of the above technical solution: the thickness of each layer of mixed powder in the N layers of mixed powder is the same.

[0013] As a further optimization of the above technical solution: the heating rate of spark plasma sintering is 60-100°C / min, the sintering temperature is 1350-1500°C, the holding time is 12-18min, and the sintering pressure is 30-45Mpa.

[0014] As a further optimization of the above technical solution: Step S1 specifically comprises: taking titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes as raw materials, using anhydrous ethanol as a ball milling medium, ball milling, mixing and drying to obtain the mixed powder.

[0015] As a further optimization of the above technical solution: the sizes of the raw materials are: titanium carbonitride: 0.62μm, tungsten carbide: 200nm, cobalt: 50nm, molybdenum carbide 1-3μm, multi-walled carbon nanotube length 0.5-2μm, diameter <8nm.

[0016] As a further optimization of the above technical solution: the ball mill for ball milling and mixing is a high-energy ball mill, a planetary ball mill or a hard alloy ball mill.

[0017] As a further optimization of the above technical solution: the ball milling mixing time is 20-24 hours, the drying temperature after ball milling is 65-75°C, and the drying time is 12-16 hours.

[0018] A gradient MWCNTs-Ti(C, N) based cermet prepared by the above method.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention prepares metal ceramics by spark plasma sintering, increases the content of multi-walled carbon nanotubes layer by layer according to a gradient path, optimizes the alloy microstructure, and has high microstructural uniformity of the obtained metal ceramics, and the fracture toughness and hardness at different positions are relatively close, and the alloy performance is superior. Compared with the method of directly adding multi-walled carbon nanotubes to the raw materials, the present invention further improves the fracture toughness and hardness of the obtained metal ceramics.

[0021] By setting a multi-layer gradient to increase the content of multi-walled carbon nanotubes layer by layer, the crack propagation resistance is enhanced layer by layer, the energy at the crack tip is effectively consumed, and the crack is inhibited from propagating inward, thereby increasing the fracture toughness of the sample and extending its service life.

[0022] The multi-layer multi-walled carbon nanotube gradient is set according to the content to enhance the bonding strength between the layers. At the same time, the multi-layer gradient is used to reduce the pulse current required for the spark plasma sintering process, increase the heating rate, improve production efficiency, and reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Example 1;

[0024] Figure 2 is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Example 3;

[0025] Figure 3 is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Example 4;

[0026] Figure 4 is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Example 6;

[0027] Figure 5 This is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Comparative Example 4;

[0028] Figure 6 This is a 30,000-fold scanning electron microscope image of the lower surface of the sample in Comparative Example 4;

[0029] Figure 7 This is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Comparative Example 1;

[0030] Figure 8 This is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Comparative Example 2;

[0031] Fig. 9 This is a 30,000-fold scanning electron microscope image of the upper surface of the sample in Comparative Example 3. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts not described and disclosed in detail in the following embodiments of the present invention should be understood as the prior art known or should be known to those skilled in the art, such as the specific structure and use method of spark plasma sintering equipment, high energy ball mill, and planetary ball mill.

[0033] Example 1

[0034] A method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering comprises the following steps:

[0035] S1: Prepare three mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes, and the mass percentage of multi-walled carbon nanotubes in the three mixed powders varies in a gradient. The three mixed powders are respectively recorded as mixed powder I, mixed powder II and mixed powder III. According to the mass percentage: mixed powder I consists of 64.8% Ti(C,N), 8% Co, 23% WC, 4% MO2C and 0.2% MWCNTs; mixed powder II consists of 64.8% Ti(C,N), 8% Co, 23% WC, 3.8% MO2C and 0.4% MWCNTs; mixed powder III consists of 64.8% Ti(C,N), 8% Co, 23% WC, 3.6% MO2C and 0.6% MWCNTs;

[0036] Specifically, 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.04 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a cemented carbide ball mill together with a cemented carbide ball and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball milling medium, for 20 h, and dried in a drying oven at 70° C. for 12 h to obtain mixed powder I;

[0037] 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.76 g of molybdenum carbide with a particle size of 1-3 μm, and 0.08 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a high-energy ball mill together with anhydrous ethanol for wet milling, wherein anhydrous ethanol was used as the ball milling medium, the ball milling time was 20 h, and after ball milling, the mixture was dried in a drying oven at 70° C. for 12 h to obtain mixed powder II;

[0038] 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.72 g of molybdenum carbide with a particle size of 1-3 μm, and 0.12 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a high-energy ball mill together with anhydrous ethanol for wet milling, wherein anhydrous ethanol was used as the ball milling medium, the ball milling time was 20 h, and after ball milling, the mixture was dried in a drying oven at 70° C. for 12 h to obtain mixed powder III;

[0039] S2: Pour mixed powder I, mixed powder II and mixed powder III into a mold layer by layer to obtain three layers of mixed powder, the thickness ratio of the three layers of mixed powder is 1:1:1. In this embodiment, the thickness of each layer of mixed powder is 1 mm, and the three layers of mixed powder are pre-pressed to obtain a metal ceramic body;

[0040] S3: Place the metal ceramic ligand into a spark plasma sintering device, apply current from the side with the lowest multi-walled carbon nanotube content in the metal ceramic body (i.e., mixed powder I), and perform spark plasma sintering on the metal ceramic body. The vacuum degree in the furnace chamber is lower than 8Pa; the sintering temperature is 1350℃; the heating rate is 75℃ / min; the holding time is 16min; and the sintering pressure is 35MPa, so as to obtain a three-layer gradient MWCNTs-Ti(C,N) based metal ceramic.

[0041] The prepared three-layer gradient MWCNTs-Ti(C,N) based cermet is recorded as sample 1, and its performance is tested: the Vickers hardness of the upper and lower surfaces of sample 1 is 1989.3 kgf / mm 2 and 1971.8kgf / mm 2 The fracture toughness of the upper and lower surfaces is 10.85 MPa·m 1 / 2 and 10.78MPa·m 1 / 2 ; The density of the sample is 6.438g / cm 3 The microstructure of the sample is uniform and there are few pores.

[0042] Example 2

[0043] A method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering comprises the following steps:

[0044] S1: Prepare three mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes, and the mass percentage of multi-walled carbon nanotubes in the three mixed powders varies gradually. The three mixed powders are respectively recorded as mixed powder I, mixed powder II and mixed powder III. According to the mass percentage, mixed powder I consists of 64.8% Ti(C,N), 8% Co, 23% WC, 4% MO2C and 0.2% MWCNTs; mixed powder II consists of 64.8% Ti(C,N), 8% Co, 22.8% WC, 4% MO2C and 0.4% MWCNTs; mixed powder III consists of 64.8% Ti(C,N), 8% Co, 22.6% WC, 4% MO2C and 0.6% MWCNTs;

[0045] Specifically, 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.04 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a cemented carbide ball mill together with a cemented carbide ball and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball milling medium, for 20 h, and dried in a drying oven at 65° C. for 16 h to obtain mixed powder I;

[0046] 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.56 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.08 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a high-energy ball mill together with anhydrous ethanol for wet milling, wherein anhydrous ethanol was used as the ball milling medium, the ball milling time was 20 h, and after ball milling, the mixture was dried in a drying oven at 65° C. for 16 h to obtain mixed powder II;

[0047] 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.52 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.12 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a high-energy ball mill together with anhydrous ethanol for wet milling, wherein anhydrous ethanol was used as the ball milling medium, the ball milling time was 20 h, and after ball milling, the mixture was dried in a drying oven at 65° C. for 16 h to obtain mixed powder III;

[0048] S2: Pour mixed powder I, mixed powder II and mixed powder III into a mold layer by layer to obtain three layers of mixed powder, the thickness ratio of the three layers of mixed powder is 1:1:1. In this embodiment, the thickness of each layer of mixed powder is 1 mm, and the three layers of mixed powder are pre-pressed to obtain a metal ceramic body;

[0049] S3: Place the metal ceramic ligand in a spark plasma sintering device, apply current from the side with the lowest multi-walled carbon nanotube content in the metal ceramic body (i.e., mixed powder I), and perform spark plasma sintering on the metal ceramic body. The vacuum degree in the furnace chamber is lower than 8Pa; the sintering temperature is 1400℃; the heating rate is 75℃ / min; the holding time is 16min; and the sintering pressure is 35MPa, so as to obtain a three-layer gradient MWCNTs-Ti(C,N) based metal ceramic.

[0050] The prepared three-layer gradient MWCNTs-Ti(C,N) based cermet is recorded as sample 2, and its performance is tested: the Vickers hardness of the upper and lower surfaces of sample 2 is 1988.5 kgf / mm 2 and 1980.9kgf / mm 2 The fracture toughness of the upper and lower surfaces is 10.09 MPa·m 1 / 2 and 10.14MPa·m 1 / 2 ; The density of the sample is 6.419g / cm 3 The microstructure of the specimen is uniform, with no obvious pores or defects.

[0051] Example 3

[0052] A method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering comprises the following steps:

[0053] S1: Three mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes were prepared, and the mass percentages of multi-walled carbon nanotubes in the three mixed powders varied in a gradient manner. The three mixed powders were respectively recorded as mixed powder I, mixed powder II and mixed powder III. According to the mass percentage, mixed powder I consisted of 64.8% Ti(C,N), 8% Co, 23% WC, 4% MO2C and 0.2% MWCNTs; mixed powder II consisted of 64.6% Ti(C,N), 8% Co, 23% WC, 4% MO2C and 0.4% MWCNTs; mixed powder III consisted of 64.4% Ti(C,N), 8% Co, 23% WC, 4% MO2C and 0.6% MWCNTs;

[0054] Specifically, 12.96 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.04 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a cemented carbide ball mill together with a cemented carbide ball and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball milling medium, for 20 h, and dried in a drying oven at 70° C. for 12 h to obtain mixed powder I;

[0055] 12.92 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.08 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a high-energy ball mill together with anhydrous ethanol for wet milling, wherein anhydrous ethanol was used as the ball milling medium, the ball milling time was 20 h, and after ball milling, the mixture was dried in a drying oven at 70° C. for 12 h to obtain mixed powder II;

[0056] 12.88 g of titanium carbonitride with a particle size of 0.62 μm, 4.6 g of tungsten carbide with a particle size of 200 nm, 1.6 g of cobalt with a particle size of 50 nm, 0.8 g of molybdenum carbide with a particle size of 1-3 μm, and 0.12 g of multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of less than 8 nm were put into a high-energy ball mill together with anhydrous ethanol for wet milling, wherein anhydrous ethanol was used as the ball milling medium, the ball milling time was 20 h, and after ball milling, the mixture was dried in a drying oven at 70° C. for 12 h to obtain mixed powder III;

[0057] S2: Pour mixed powder I, mixed powder II and mixed powder III into a mold layer by layer to obtain three layers of mixed powder, the thickness ratio of the three layers of mixed powder is 1:1:1. In this embodiment, the thickness of each layer of mixed powder is 1 mm, and the three layers of mixed powder are pre-pressed to obtain a metal ceramic body;

[0058] S3: Place the metal ceramic ligand into a spark plasma sintering device, apply current from the side with the lowest multi-walled carbon nanotube content in the metal ceramic body (i.e., mixed powder I), and perform spark plasma sintering on the metal ceramic body. The vacuum degree in the furnace chamber is lower than 8Pa; the sintering temperature is 1350℃; the heating rate is 75℃ / min; the holding time is 16min; and the sintering pressure is 35MPa, so as to obtain a three-layer gradient MWCNTs-Ti(C,N) based metal ceramic.

[0059] The prepared three-layer gradient MWCNTs-Ti (C, N) based cermet is recorded as sample 3, and its performance is tested: the Vickers hardness of the upper and lower surfaces of sample 3 is 1890.97 kgf / mm 2and 1892.3kgf / mm 2 The fracture toughness of the upper and lower surfaces is 10.84 MPa·m 1 / 2 and 10.61MPa·m 1 / 2 ; The density of the sample is 6.410g / cm 3 The specimen has a uniform structure and few defects.

[0060] Example 4

[0061] A method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering comprises the following steps:

[0062] S1: Five mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes are prepared, and the mass percentages of the multi-walled carbon nanotubes in the five mixed powders vary in a gradient. The five mixed powders are respectively recorded as mixed powder I, mixed powder II, mixed powder III, mixed powder IV and mixed powder V. The components of the mixed powders are shown in Table 1 according to mass percentage:

[0063] Table 1

[0064] Specifically, titanium carbonitride with a particle size of 0.62 μm, tungsten carbide with a particle size of 200 nm, cobalt with a particle size of 50 nm, molybdenum carbide with a particle size of 1-3 μm, and multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of <8 nm were weighed according to the weights in Table 2 below, put into a cemented carbide ball mill, and wet milled for mixing using anhydrous ethanol as the ball milling medium. The ball milling time was 20 h. After ball milling, the mixture was dried in a drying oven at 70 ° C for 12 h to obtain the corresponding mixed powders I, II, III, IV, and V.

[0065] Table 2

[0066] S2: Pour mixed powder I, mixed powder II, mixed powder III, mixed powder IV and mixed powder V into a mold layer by layer to obtain five layers of mixed powder, the thickness ratio of the five layers of mixed powder is 1:1:1:1:1. In this embodiment, the thickness of each layer of mixed powder is 0.6 mm. The five layers of mixed powder are pre-pressed to obtain a metal ceramic body;

[0067] S3: Place the metal ceramic ligand into a spark plasma sintering device, apply current from the side with the lowest multi-walled carbon nanotube content in the metal ceramic body (i.e., mixed powder I), and perform spark plasma sintering on the metal ceramic body. The vacuum degree in the furnace chamber is lower than 8Pa; the sintering temperature is 1350℃; the heating rate is 75℃ / min; the holding time is 16min; and the sintering pressure is 35MPa, so as to obtain a five-layer gradient MWCNTs-Ti(C,N) based metal ceramic.

[0068] The five-layer gradient MWCNTs-Ti(C,N)-based cermet prepared was recorded as sample 5, and its performance was tested: the Vickers hardness of the upper and lower surfaces of sample 5 was 1975.1 kgf / mm 2 and 1964.1kgf / mm 2 The fracture toughness of the upper and lower surfaces is 9.84 MPa·m 1 / 2 and 9.75MPa·m 1 / 2 The density of the sample is 6.412 g / cm 3 .

[0069] Example 5

[0070] A method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering comprises the following steps:

[0071] S1: Five mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes were prepared, and the mass percentages of the multi-walled carbon nanotubes in the five mixed powders varied in a gradient manner. The five mixed powders were respectively recorded as mixed powder I, mixed powder II, mixed powder III, mixed powder IV and mixed powder V. The components of the mixed powders were shown in Table 3 according to mass percentage:

[0072] Table 3

[0073] Specifically, titanium carbonitride with a particle size of 0.62 μm, tungsten carbide with a particle size of 200 nm, cobalt with a particle size of 50 nm, molybdenum carbide with a particle size of 1-3 μm, and multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of <8 nm were weighed according to the weights shown in Table 4 below, put into a cemented carbide ball mill, and wet milled for mixing using anhydrous ethanol as the ball milling medium. The ball milling time was 20 h. After ball milling, the mixture was dried in a drying oven at 65 ° C for 16 h to obtain the corresponding mixed powders I, II, III, IV, and V.

[0074] Table 4

[0075] S2: Pour mixed powder I, mixed powder II, mixed powder III, mixed powder IV and mixed powder V into a mold layer by layer to obtain five layers of mixed powder, the thickness ratio of the five layers of mixed powder is 1:1:1:1:1. In this embodiment, the thickness of each layer of mixed powder is 0.6 mm. The five layers of mixed powder are pre-pressed to obtain a metal ceramic body;

[0076] S3: Place the metal ceramic ligand into a spark plasma sintering device, apply current from the side with the lowest multi-walled carbon nanotube content in the metal ceramic body (i.e., mixed powder I), and perform spark plasma sintering on the metal ceramic body. The vacuum degree in the furnace chamber is lower than 8Pa; the sintering temperature is 1400℃; the heating rate is 80℃ / min; the holding time is 16min; and the sintering pressure is 30MPa, so as to obtain a five-layer gradient MWCNTs-Ti(C,N) based metal ceramic.

[0077] The five-layer gradient MWCNTs-Ti(C,N)-based cermet prepared was recorded as sample 5, and its performance was tested: the Vickers hardness of the upper and lower surfaces of sample 5 was 2030.6 kgf / mm 2 and 2024.2kgf / mm 2 The fracture toughness of the upper and lower surfaces is 9.78 MPa·m 1 / 2 and 9.71MPa·m 1 / 2 The density of the sample is 6.474 g / cm 3 The sample structure is uniform, without obvious defects and pores.

[0078] Example 6

[0079] A method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering comprises the following steps:

[0080] S1: Five mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes were prepared, and the mass percentages of the multi-walled carbon nanotubes in the five mixed powders varied in a gradient manner. The five mixed powders were respectively recorded as mixed powder I, mixed powder II, mixed powder III, mixed powder IV and mixed powder V. The components of the mixed powders were shown in Table 5 according to mass percentage:

[0081] Table 5

[0082] Specifically, titanium carbonitride with a particle size of 0.62 μm, tungsten carbide with a particle size of 200 nm, cobalt with a particle size of 50 nm, molybdenum carbide with a particle size of 1-3 μm, and multi-walled carbon nanotubes with a length of 0.5-2 μm and a diameter of <8 nm were weighed according to the weights shown in Table 6 below, put into a cemented carbide ball mill, and wet milled for mixing using anhydrous ethanol as the ball milling medium. The ball milling time was 20 h. After ball milling, the mixture was dried in a drying oven at 70 ° C for 12 h to obtain the corresponding mixed powders I, II, III, IV, and V.

[0083] Table 6

[0084] S2: Pour mixed powder I, mixed powder II, mixed powder III, mixed powder IV and mixed powder V into a mold layer by layer to obtain five layers of mixed powder, the thickness ratio of the five layers of mixed powder is 1:1:1:1:1. In this embodiment, the thickness of each layer of mixed powder is 0.6 mm. The five layers of mixed powder are pre-pressed to obtain a metal ceramic body;

[0085] S3: Place the metal ceramic ligand into a spark plasma sintering device, apply current from the side with the lowest multi-walled carbon nanotube content in the metal ceramic body (i.e., mixed powder I), and perform spark plasma sintering on the metal ceramic body. The vacuum degree in the furnace chamber is lower than 8Pa; the sintering temperature is 1400℃; the heating rate is 75℃ / min; the holding time is 18min; and the sintering pressure is 30MPa, so as to obtain a five-layer gradient MWCNTs-Ti(C,N) based metal ceramic.

[0086] The five-layer gradient MWCNTs-Ti(C,N)-based cermet prepared was recorded as sample 5, and its performance was tested: the Vickers hardness of the upper and lower surfaces of sample 5 was 1974.7 kgf / mm 2 and 1975.9kgf / mm 2 The fracture toughness of the upper and lower surfaces is 10.84 MPa·m 1 / 2 and 10.65MPa·m 1 / 2 ; The density of the sample is 6.423g / cm 3 .

[0087] Comparative Example 1

[0088] According to the mass percentage of 64.8% Ti(C,N), 8% Co, 23% WC, 4% MO2C, and 0.2% MWCNTs, 12.96g of titanium carbonitride with a particle size of 0.62μm, 4.6g of tungsten carbide with a particle size of 200nm, 1.6g of cobalt with a particle size of 50nm, 0.8g of molybdenum carbide with a particle size of 1-3μm, and 0.04g of multi-walled carbon nanotubes with a length of 0.5-2μm and a diameter of less than 8nm were weighed, put into a cemented carbide ball mill together with cemented carbide balls and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball. Grinding medium, ball milling time is 20h, after ball milling, dry in a drying oven at 70℃ for 12h; and pour the dried powder into a mold, the thickness of the obtained powder layer is 3mm, the powder layer is pre-pressed into shape, and placed in a spark plasma sintering equipment for sintering, the vacuum degree in the furnace chamber is less than 8Pa; the sintering temperature is 1350℃; the heating rate is 75℃ / min; the holding time is 16min; the sintering pressure is 35MPa, and Ti(C,N)-based metal ceramics are prepared by sintering.

[0089] The Ti(C,N)-based cermet prepared by sintering in this comparative example is recorded as comparative sample 1, and its performance is tested: the Vickers hardness of the upper surface of comparative sample 1 is 1845.5 kgf / mm 2 , the Vickers hardness of the lower surface is 1774.3kgf / mm 2 ; The fracture toughness of the upper and lower surfaces is 9.55MPa·m 1 / 2 , 9.17MPa·m 1 / 2 The microstructure of the specimen is not uniform, and the properties of the upper and lower surfaces of the alloy are quite different.

[0090] Comparative Example 2

[0091] According to the mass percentage of 64.6% Ti(C,N), 8% Co, 23% WC, 4% MO2C, and 0.4% MWCNTs, 12.92g of titanium carbonitride with a particle size of 0.62μm, 4.6g of tungsten carbide with a particle size of 200nm, 1.6g of cobalt with a particle size of 50nm, 0.8g of molybdenum carbide with a particle size of 1-3μm, and 0.08g of multi-walled carbon nanotubes with a length of 0.5-2μm and a diameter of less than 8nm were weighed, put into a cemented carbide ball mill together with cemented carbide balls and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball. Grinding medium, ball milling time is 20h, after ball milling, dry in a drying oven at 70℃ for 12h; and pour the dried powder into a mold, the thickness of the obtained powder layer is 3mm, the powder layer is pre-pressed into shape, and placed in a spark plasma sintering equipment for sintering, the vacuum degree in the furnace chamber is less than 8Pa; the sintering temperature is 1350℃; the heating rate is 75℃ / min; the holding time is 16min; the sintering pressure is 35MPa, and Ti(C,N)-based metal ceramics are prepared by sintering.

[0092] The Ti(C,N)-based cermet prepared by sintering in this comparative example is recorded as comparative sample 2, and its performance is tested: the Vickers hardness of the upper surface of comparative sample 2 is 1863.6 kgf / mm 2 , the lower surface Vickers hardness is 1775.1kgf / mm 2 ; The fracture toughness of the upper and lower surfaces is 9.62MPa·m 1 / 2 , 9.16MPa·m 1 / 2 The properties of the upper and lower surfaces of the alloy are quite different.

[0093] Comparative Example 3

[0094] According to the mass percentage of 64.4% Ti(C,N), 8% Co, 23% WC, 4% MO2C, and 0.6% MWCNTs, 12.88g of titanium carbonitride with a particle size of 0.62μm, 4.6g of tungsten carbide with a particle size of 200nm, 1.6g of cobalt with a particle size of 50nm, 0.8g of molybdenum carbide with a particle size of 1-3μm, and 1.2g of multi-walled carbon nanotubes with a length of 0.5-2μm and a diameter of less than 8nm were weighed, put into a cemented carbide ball mill together with cemented carbide balls and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball. Grinding medium, ball milling time is 20h, after ball milling, dry in a drying oven at 70℃ for 12h; and pour the dried powder into a mold, the thickness of the obtained powder layer is 3mm, the powder layer is pre-pressed into shape, and placed in a spark plasma sintering equipment for sintering, the vacuum degree in the furnace chamber is less than 8Pa; the sintering temperature is 1350℃; the heating rate is 75℃ / min; the holding time is 18min; the sintering pressure is 30MPa, and Ti(C,N)-based metal ceramics are prepared by sintering.

[0095] The Ti(C,N)-based cermet prepared by sintering in this comparative example is recorded as comparative sample 3, and its performance is tested: the Vickers hardness of the upper and lower surfaces of comparative sample 3 is 1844.7 kgf / mm 2 and 1758.3kgf / mm 2 The fracture toughness of the upper and lower surfaces is 10.03MPa·m 1 / 2 and 9.28MPa·m 1 / 2 .

[0096] Comparative Example 4

[0097] According to the mass percentage of 65% Ti(C,N), 8% Co, 23% WC, and 4% MO2C, 13g of titanium carbonitride with a particle size of 0.62μm, 4.6g of tungsten carbide with a particle size of 200nm, 1.6g of cobalt with a particle size of 50nm, and 0.8g of molybdenum carbide with a particle size of 1-3μm were weighed, put into a cemented carbide ball mill together with cemented carbide balls and anhydrous ethanol, and ball milled and mixed by wet milling, with anhydrous ethanol as the ball milling medium. The time is 20 hours. After ball milling, it is dried in a drying oven at 70°C for 12 hours. The dried powder is poured into a mold. The thickness of the obtained powder layer is 3 mm. The powder layer is pre-pressed into shape and placed in a spark plasma sintering device for sintering. The vacuum degree in the furnace chamber is less than 8 Pa. The sintering temperature is 1400°C; the heating rate is 75°C / min; the holding time is 16 minutes; the sintering pressure is 35 MPa, and Ti(C,N)-based metal ceramics are prepared by sintering.

[0098] The Ti(C,N)-based cermet prepared by sintering in this comparative example is recorded as comparative sample 4, and its performance is tested: the Vickers hardness of the upper and lower surfaces of comparative sample 4 is 1823.1 kgf / mm 2 and 1729.7kgf / mm 2 The fracture toughness of the upper and lower surfaces is 8.27 and 8.53 MPa·m 1 / 2 The sintered microstructure of the sample without adding multi-walled carbon nanotubes was uneven and the performance was poor.

[0099] Analysis of sample performance test results:

[0100] Comparative Examples 1-4 Compared with Example 3, different proportions of multi-walled carbon nanotubes were added in Comparative Examples 1-3, but no gradient layer was set according to the content of the multi-walled carbon nanotubes, and Comparative Example 4 did not add multi-walled carbon nanotubes.

[0101] The mass percentages of multi-walled carbon nanotubes in Comparative Examples 1, 2, and 3 are 0.2%, 0.4%, and 0.6%, respectively, which are the same as one of the three-layer gradient layers in Example 3. The fracture toughness of the upper and lower surfaces of Example 3 is 10.84 MPa·m 1 / 2 and 10.61MPa·m 1 / 2 The Vickers hardness of the upper and lower surfaces is 1890.97kgf / mm 2 and 1892.3kgf / mm 2 The fracture toughness of the upper and lower surfaces of comparative example 1 are 9.55 MPa·m 1 / 2 , 9.17MPa·m 1 / 2 The Vickers hardness of the upper surface is 1845.5kgf / mm 2 , the Vickers hardness of the lower surface is 1774.3kgf / mm 2; The fracture toughness of the upper and lower surfaces of Comparative Example 2 is 9.62MPa·m 1 / 2 , 9.16MPa·m 1 / 2 The Vickers hardness of the upper surface is 1863.6kgf / mm 2 , the lower surface Vickers hardness is 1775.1kgf / mm 2 ; The fracture toughness of the upper and lower surfaces of Comparative Example 3 is 10.03MPa·m 1 / 2 and 9.28MPa·m 1 / 2 The Vickers hardness of the upper and lower surfaces is 1844.7kgf / mm 2 and 1758.3kgf / mm 2 The fracture toughness of the upper and lower surfaces of comparative example 4 is 8.27 and 8.53 MPa·m 1 / 2 The Vickers hardness of the upper and lower surfaces is 1823.1kgf / mm 2 and 1729.7kgf / mm 2 .

[0102] It can be seen from this that the addition of multi-walled carbon nanotubes in Comparative Examples 1-3 improves the fracture toughness of the prepared metal ceramics to a certain extent, and as the amount of multi-walled carbon nanotubes added increases, the fracture toughness shows an overall increasing trend, but the fracture toughness of the metal ceramics prepared in Comparative Examples 1-3 is weaker than that of Example 3, indicating that Example 3 adopts a gradient arrangement of multi-walled carbon nanotubes, which improves the fracture toughness of the prepared samples without increasing the amount of carbon nanotubes added; similarly, Example 3 also improves the Vickers hardness of the prepared samples without increasing the amount of carbon nanotubes added.

[0103] In comparative examples 1-3, the differences in fracture toughness and Vickers hardness between the upper and lower surfaces are quite obvious, and the difference in fracture toughness between the upper and lower surfaces is 0.38 MPa·m 1 / 2 Above, the difference in Vickers hardness is 50kgf / mm 2 In Example 3, the multi-walled carbon nanotubes are arranged in a gradient manner, and the difference in fracture toughness between the upper and lower surfaces of the prepared sample is 0.23 MPa·m 1 / 2 , the difference in Vickers hardness is 1.33kgf / mm 2 Combined with the test results of Examples 1, 2, 4, 5, and 6, it can be seen that the difference in fracture toughness between the upper and lower surfaces of the samples prepared by the preparation method of the present invention does not exceed 0.25 MPa·m 1 / 2 , the difference in Vickers hardness does not exceed 20kgf / mm 2 , indicating that by arranging multi-walled carbon nanotubes in a gradient pattern, the fracture toughness and hardness at different positions of the prepared samples can be made closer, thereby improving the performance of the alloy.

[0104] The microstructure of the prepared samples was observed. Figure 1-4 It can be seen that the microstructure of the sample prepared by the method of the present invention is uniform and has few pores. Figure 5-9 It can be seen that the microstructures of Comparative Examples 1-4 are not uniform. It can also be inferred that the alloy properties of the sample prepared in Comparative Example 4 are weaker than those of the sample prepared in Example 3.

[0105] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering, characterized in that: The following steps are involved: S1: preparing N kinds of mixed powders consisting of titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes, N≧3, and the mass percentage of the multi-walled carbon nanotubes in the N kinds of mixed powders changes in a gradient; S2: laying the mixed powder layer by layer according to the change gradient of the multi-walled carbon nanotubes, and pre-pressing the obtained N layers of mixed powder to obtain a metal ceramic body; S3: applying current from the side of the metal ceramic body with the lowest multi-walled carbon nanotube content to perform spark plasma sintering on the metal ceramic body to obtain the gradient MWCNTs-Ti(C,N) based metal ceramic.

2. The method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering according to claim 1, characterized in that: According to mass percentage, the mixed powder consists of 64.2-65% titanium carbonitride, 22.4-23.2% tungsten carbide, 8% cobalt, 3.6-4.4% molybdenum carbide and 0.2-0.6% multi-walled carbon nanotubes.

3. The method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering according to claim 1, characterized in that: The gradient of the multi-walled carbon nanotubes is 0.1% or 0.2%.

4. The method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering according to claim 1, characterized in that: The thickness of each layer of mixed powder in the N layers of mixed powder is the same.

5. The method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering according to claim 1, characterized in that: The heating rate of spark plasma sintering is 60-100°C / min, the sintering temperature is 1350-1500°C, the holding time is 12-18min, and the sintering pressure is 30-45Mpa.

6. The method for preparing gradient MWCNTs-Ti(C,N) based cermet by spark plasma sintering according to claim 1, characterized in that: Step S1 specifically comprises: taking titanium carbonitride, tungsten carbide, cobalt, molybdenum carbide and multi-walled carbon nanotubes as raw materials, using anhydrous ethanol as a ball milling medium, ball milling, mixing and drying to obtain the mixed powder.

7. A method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering as claimed in claim 6, characterized in that: The sizes of the raw materials are: titanium carbonitride: 0.62 μm, tungsten carbide: 200 nm, cobalt: 50 nm, molybdenum carbide 1-3 μm, multi-walled carbon nanotubes 0.5-2 μm in length and less than 8 nm in diameter.

8. A method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering as claimed in claim 6, characterized in that: The ball mill for ball milling and mixing is a high energy ball mill, a planetary ball mill or a hard alloy ball mill.

9. A method for preparing gradient MWCNTs-Ti(C,N) based cermets by spark plasma sintering as claimed in claim 6, characterized in that: The ball milling mixing time is 20-24 hours, the drying temperature after ball milling is 65-75°C, and the drying time is 12-16 hours.

10. A gradient MWCNTs-Ti(C,N) based cermet obtained by the method according to any one of claims 1 to 9.